An Empirical Study On The Relationship Between Directors' Remuneration And Corporate Capital Structure As Well As The Performance Of Public Listed Companies In Malaysia - Tong, Lin Yong (2003)
This study of the relationship between directors' compensation and the corporate strenght of the public listed companies in Malaysia has served as an empirical test for the significance and the correlation of that relationship.